1900-1984. - Maurice Keitelman Gallery, Brussel (Brussel : Maurice Keitelman Gallery, 1984)
Arman ; Basquiat, Jean-Michel ; Bourdelle, Emile-Antoine ; Delahaut, Jo ; Dubuffet, Jean ; Fautrier, Jean ; González, Julio ; Haring, Keith ; Heymans, Adriaan-Josef ; Joostens, Paul ; Labisse, Félix ; Lady Pink ; Magritte, René ; Schmalix, Hubert ; Stobbaerts, Marcel ; Tadini, Emilio ; Toxic ; Uecker, Günther ; Velickovic, Vladimir ; Wyckaert, Maurice ; Zadkine, Ossip ; Zimmer, Bernd
Frans
1900-1984, Maurice Keitelman Gallery Brussel, du 17 octobre au 30 novembre 1984
boek